Attitudes, knowledge and beliefs around homosexuality: exploring the views of 5th year medical students - Sopitshi, Athenkosi (Department of Public Health and Family Medicine, 2017)
Introduction: Discrimination from health workers has been found to be a deterrent for lesbian, gay, bisexual and transgender (LGBTI) people seeking healthcare. Despite these findings, LGBTI-focused healthcare remains understated in medical training and university curricular. Learning about medical students' attitudes can provide useful ways of identifying interventions to capacitate health professionals to address LGBTI health. Methods: This study is a mixed methods study, data were collected using a 25 item homophobia scale with additional questions designed for the South African context, and focus group discussions with semi-structured questions. Results: 157 Medical students in the 5th year class at a university in the Western Cape, South Africa completed the survey, 20 of them formed part of three focus group discussions. Outcomes showed significant gaps in student's curriculum in the area of LGBTI health which influenced their lack of knowledge and preparedness. Considering that homophobia and heterosexism remain widespread in the students' contexts, the findings point to generally favourable views of LGBTI people. In this respect, two thirds of the participants indicated that they are not bothered by seeing same-sex partners together and 64% felt that homosexuality was not immoral and showed support for LGBTI rights. The qualitative findings indicate that a contributing factor in shifting their attitudes based on their own perspectives was a change in environments from their hometowns to university. Students showed a keen interest in early integration of LGBTI health in their curriculum which is encouraging. Conclusion: Medical training needs to be responsive and intentional about addressing student attitudes towards LGBTI people, as this has implications on the students' perceived competency and affects the quality of healthcare they deliver.